FARMER SATISFACTION THROUGH FARMER GROUP PERFORMANCE: A STUDY IN SWAMPLAND, SOUTH KALIMANTAN - Marhamah, Binti Tsaniatul; Masyhuri, Masyhuri; Waluyati, Lestari Rahayu (Jurnal Aplikasi Manajemen, 2020)
The government is conducting a program that more concerned with the presence of leak swamp called SERASI (Save the Peasant Welfare Farmers) for rice farmers, by providing various assistance including production input and other supporting activities such as education for farmers and the development of agricultural institutions. The existence of farmer groups has a positive influence on the sustainability of leak swamp farming, but it doesn't deny the shortcomings felt by farmers in the management and performance of the farmer groups. This research was conducted to determine farmers satisfaction with the performance of farmer groups and find various steps and strategies from internal management factors to develop farmer groups so that they can work better in supporting both government programs and farmer's welfare with Analysis methods of IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index). Data collection involved 42 farmers using a questionnaire. The results showed that farmers were satisfied with the performance of the farmer group with a value of 67.21% and they had to prioritize internal management in the group, namely Statutes/Articles of Association, vision, and mission, organizational structure, work plan, administration, financial records, training, superior seed, integrated pest control, granting credit and the latest information.